Neonatal mortality post ISIS conflict in Iraq - Bash, Sally S.; AL-Kaseer, Eman A. (Journal of the Faculty of Medicine Baghdad, 2018)
Neonatal mortality is an indicator to assess maternal and neonatal care.1 Iraq has been suffering from wars, economic hardship, terrorism and internal displacement for last 4 decades.2 The impact of such suffering on health was reported.3 However, the impact of terrorism on health infrastructure which in turn manifested in neonatal mortality was neglected. This study carried out to demonstrate the effect of war against terrorism on neonatal mortality in Iraq.